THE OPTIMAL COMPOSITIONS OF DAILY MENU FOOD FOR BREASTFEEDING MOTHERS USING THE SIMPLEX METHOD - Adin Lazuardy Firdiansyah (Barekeng)
In this research, we want to find the optimal compositions of the daily food menu for breastfeeding mothers at the minimum cost. These problems are formed into linear programs by including some available data, like the price of food in the traditional market, the nutritional content of each food, and the recommended nutritional adequacy rate. After that, we count the linear programs by using the Simplex method with the help of the LINDO solver. The output of this research is the weight of food consumed by mothers to meet their daily nutritional needs. Based on the data collected, we obtain the 36 food combinations that include the staple type of food (rice), the type of side dishes (pindang fish, tilapia fish, mackerel tuna, chicken eggs), the type of vegetables (cassava leaves, katuk leaves, moringa leaves), the type of fruits (melon, watermelon, orange), and the type of nut (peanuts). Next, we analyze the model according to the groups of breastfeeding mothers in the first and second 6 months. From this research, we obtain that the optimal compositions of the daily food menu for breastfeeding mothers in the first 6 months are cassava leaves. Meanwhile, the optimal compositions of the daily food menu in the second 6 months are rice and cassava leaves.